The Social Construction of Lesbian Community in Kendari City, Indonesia - Ambo Upe; Syaifudin S. Kasim; Hariati (International Journal of Qualitative Research, 2022)
Lesbian is one of the global issues in gender relations and sexual relations. On the one hand, it threatens the existence of social order, and on the other, it becomes a space for human rights struggle for the homosexual community. Therefore, this research aims to determine the construction process of the lesbian community in Kendari City. This research uses a qualitative descriptive method with data collection techniques, namely interviews and documentation. The study showed that lesbian behavior in Kendari City did not occur naturally but resulted from social construction in three moments: externalization, objectivation, and internalization. The moment of externalization is expressed mentally and physically in the form of homosexual relationships with fellow women with the same sexual orientation. The expression of lesbians in everyday life then experiences habituation in the form of community as an objective social world. Furthermore, the re-absorption (internalization) of the objective world into subjective consciousness through social media (Facebook) and personal socialization.